(untitled) (Journal of Parents and Teachers, 2014)
The disappearance of the playful element of sport has led to a criticism of its conception as a spectacle because of demonstrations by enthusiastic audiences and how their behavior reflects on what sport really is. In schools, where sport should maintain its purity and essence, terms such as "professionalization" and "spectacle" should be avoided. Physical education should be connected to the dimension of "knowing how to be". Various risk factors for violence are explained, such as family attitude towards sports, the child’s sporting environment and the role of the child’s coach, as well as how violent behavior in school sport can be curbed.